Dynamic conductivity of polymer dielectrics under time-varying temperature field. (5th June 2019) - Qin, Sichen; Tu, Youping; Chen, Bingying; Xu, Duohu; Li, Chuanyang; Tan, Tian
Abstract: We succeeded in putting forward a two-dimensional electric transport model based on the first-order kinetic charge trapping/detrapping model. The dynamic conductivity under thermal cycle of polyimide is analyzed from numerical calculations and experimental tests. The conductivity characteristics of polymer dielectric under temperature cycling was found to be dominated by temperature and time, because of filled traps and rapid changes in temperature. The present study contributes in providing an accurate conductivity calculation model for polymer dielectrics under temperature-varying fields.